2019
DOI: 10.1155/2019/1067473
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Trial to Compare Direct and Indirect Laryngoscopy Using C-MAC PM® with Macintosh Blade and D-Blade® in a Simulated Difficult Airway

Abstract: Objective. Evaluation of C-MAC PM® in combination with a standard Macintosh blade size 3 in direct and indirect laryngoscopy and D-Blade® in indirect laryngoscopy in a simulated difficult airway. Primary outcome was defined as the best view of the glottic structures. Secondary endpoints were subjective evaluation and assessment of the intubation process. Methods. Prospective monocentric, observational study on 48 adult patients without predictors for difficult laryngoscopy/tracheal intubation undergoing orthop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
(30 reference statements)
0
8
1
Order By: Relevance
“…These results agree with prior trials that suggested that the C-MAC D-Blade videolaryngoscope offers better glottic visualization in terms of a higher rate of CL grade I ratings compared with the McCoy laryngoscope during oropharyngeal intubation in patients who had limited neck mobility with a cervical collar [24]. These benefits on intubating condition may be explained by the pronounced curvature of the C-MAC D-Blade videolaryngoscope, which does not require alignment of oral, pharyngeal, and tracheal axes and its utility in cases of anterior placed larynx by providing an extended view of the vertical plane of the glottic areas [25,26]. The result of the present study would be applied to patients with head and neck trauma, cervical spine disorders and difficult intubation anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…These results agree with prior trials that suggested that the C-MAC D-Blade videolaryngoscope offers better glottic visualization in terms of a higher rate of CL grade I ratings compared with the McCoy laryngoscope during oropharyngeal intubation in patients who had limited neck mobility with a cervical collar [24]. These benefits on intubating condition may be explained by the pronounced curvature of the C-MAC D-Blade videolaryngoscope, which does not require alignment of oral, pharyngeal, and tracheal axes and its utility in cases of anterior placed larynx by providing an extended view of the vertical plane of the glottic areas [25,26]. The result of the present study would be applied to patients with head and neck trauma, cervical spine disorders and difficult intubation anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…Also using the Yentis 12 scale, a significant improvement in view from directly sighted to videoscopic views was reported in the cervical collar group. Raimann et al 6 also studied a small population of elective surgical patients with a cervical collar fitted, sequentially performing directly sighted laryngoscopy with the C-MAC reusable Macintosh blade, then indirectly sighted VL with the same blade. With and without ''backwards-upwards'' rightwards pressure (BURP), the videoscopic view was better than the directly sighted view in a moderate but statistically significant number of patients (defined as a change from Cormack-Lehane Grade 3 or 4 to Grade 2a, 2b or 1): six of 32 without applied BURP; seven of 25 with applied BURP; and 14 of 18 with BURP applied only during Mac-VL.…”
Section: Discussionmentioning
confidence: 99%
“…Third, our study methodology differed from some of the earlier trials by attempting to compare direct and videoscopic views at the same moment in time, with ratings done by different clinicians (the laryngoscopist and two independent videoscopic scorers), each blinded to the results recorded by the others. Fourth, only the Kaplan et al 3 Byhahn et al 5 and Raimann et al 6 studies compared the direct and videoscopic views obtained with the same Mac-VL; the Piepho and Aziz 1,2 studies documented videoscopic views obtained using the Macintosh-style C-MACÒ VL and those obtained in other patients undergoing Macintosh DL. Although unlikely, it is possible that the view obtained during regular DL may not equate exactly to direct peroral sighting using a Mac-VL, rendering a comparison of the present study with those studies invalid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 Although this scoring system is designed for patients undergoing direct laryngoscopy, previous studies have also applied the CLS to describe the laryngeal view during indirect laryngoscopy. 8 , 9 We thus felt that this would also be an appropriate system to compare changes occurring during THRIVE use. Figure 2 highlights example images of CLS ranging from grades 1 to 3.…”
Section: Methodsmentioning
confidence: 99%